Epidemiological profile of hepatitis C virus infection in patients from west region of Minas Gerais State, Brazil - Villar, Lívia Melo; Souza, Neila Paula de [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Borges, Aércio Sebastião; Garbin, Cléa Adas Saliba [UNESP] (Univ Federal Uberlandia, 2015)
Hepatitis C virus (HCV) is a serious public health problem and is the leading cause of liver transplantation due to cirrhosis and hepatocellular carcinoma. In Brazil, it is estimated that there are approximately 2 to 3 million HCV chronic carriers. Few data regarding HCV infection are available in West region of Minas Gerais State. Due to the absence of an effective vaccine against this important human pathogen and the high costs of antiviral treatment, it is important to conduct epidemiological studies with the purpose of carry out the planning and implementation of measures to prevent hepatitis C in different populations. Therefore, the aim of this study is to describe the epidemiological aspects of HCV patients from West region of Minas Gerais State, Brazil. Sociodemographic data and risk factors for HCV infection were determined from 74 HCV patients from Uberlandia city (Minas Gerais State). Reactive anti-HCV sera samples were submitted to HCV RNA and genotype detection. Most of individuals were male (63.5%) with mean age of 51 years and presenting low socioeconomic status. HCV genotype was determined among 40 samples and the frequencies were: genotype 2 (45%), 1 (37.5%) and 3 (17.5%). Hepatitis C virus (HCV) infection was common among male and low socioeconomic status individuals.

O vírus da hepatite C (HCV) é um sério problema de saúde pública e a principal causa de transplante de fígado devido à cirrose e carcinoma hepatocelular. No Brasil, estima-se que há aproximadamente 2 a 3 milhões de portadores crônicos do HCV. Poucos dados sobre a infecção pelo HCV na região oeste do estado de Minas Gerais estão disponíveis. Devido à ausência de vacina eficaz contra esse importante patógeno humano e aos altos custos do tratamento antiviral, é importante realizar estudos epidemiológicos com a finalidade de executar o planejamento e implementação de medidas para prevenir a hepatite C em diferentes populações. Portanto, o objetivo deste estudo é descrever os aspectos epidemiológicos dos pacientes portadores de HCV da região oeste do estado de Minas Gerais, Brasil. Dados sociodemográficos e fatores de risco para a infecção com HCV foram determinados de 74 pacientes portadores de HCV da cidade de Uberlândia, Minas Gerais. Amostras de soro reativas foram submetidas às detecções de HCV RNA e genótipo. A maioria dos indivíduos eram homens (63,5%) com média de idade de 51 anos e baixo nível socioeconômico. O genótipo do HCV foi determinado entre 40 amostras e as frequências foram: genótipo 2 (45%), 1 (37,5%) e 3 (17,5%). A infecção com o vírus da hepatite C foi frequente entre homens e indivíduos de baixo nível socioeconômico.
Perfil epidemiológico da infecção pelo vírus da hepatite C em pacientes da região oeste de Minas Gerais, Brasil
Keywords: Hepatitis C; Epidemiology; Public health; Hepatite C; Epidemiologia; Saúde pública